Exposition of Colombian Students to an Authentic Language Learning Context (2023)
The current study aims at implementing online pedagogical strategies to foster quality education by exposing them to native language interactions. It was carried out in a mixed context; the first was Euclides Lizarazo departmental ethno-educational institution in Magdalena Colombia and the second was English Connect in Las Vegas, United states. The research population was 15 eleven graders at the official system in Colombia and sixth students from U.S.A. This investigation was experimental with a qualitative approach and a descriptive scope. Within thisresearch, there were some unplanned findings throughout its implementation, which became important for the analysis phase, such as limited proficiency in the use of electronic devices, at least for academic purposes and/or interaction for English language development, employing collaborative language learning with native speakers and fostering self-confidence withtechnological resources, among others. Notwithstanding, this project had many positive results since it was possible to diagnose learners’ English proficiency level, design thevirtual pedagogical strategies, and analyze learners’ perception regarding the intervention in order to track their progress and define the impact. To conclude, it is essential to mention that school learners in Colombia, who learn English as a mandatory requirement, especially the ones from the official system findtheEnglishlearning useless, since, in most cases, they do not consider either work or travel with/to English-speaking countries